Selected U.S. Multinational Service Firms in Perspective - Gaedeke, Ralph M. (Journal of International Business Studies, 1973)
Indications are that advertising, consulting, and law firms are rapidly becoming as entrenched in the global market arena as their predecessors, the manufacturing and extractive industries.